Sharia Financing Making Decisions: Evaluation of Service and Regulatory Understanding Factors - Lubis, Nurliza; Harahap, Ainul Yusna; Lubis, Nasrul Kahfi (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to evaluate the factors that influence customer decisions in taking sharia financing, especially for customers who use Sharia Financing at Bank Aceh Syariah Kota Langsa Branch. The study population included 153 customers receiving subsidized mortgage housing from Bank Syariah Aceh Kota Langsa. Sampling was carried out using the purposive sampling method using the Slovin formula. Data were collected through the distribution of questionnaires to 60 respondents and analyzed using version 24 of the social science statistics package. This study used quantitative methods with multiple regression analysis. The results showed that service quality has a significant influence on customer decisions in taking Sharia KPR Subsidy financing at Bank Syariah Aceh. In addition, understanding of sharia regulations also has a significant impact on customers' decisions to make Sharia KPR Subsidy financing at Bank Syariah Aceh. The combination of service quality and regulatory understanding has a significant influence on lending decisions at Bank Aceh Syariah. The coefficient of determination test shows that service quality and regulatory understanding simultaneously have an influence of 74% on Sharia mortgage financing decisions, while the remaining 26% are influenced by other factors outside the framework of this study. This research provides a further understanding of the importance of service quality and regulatory understanding in shaping customer decisions related to sharia financing at Bank Aceh. Keywords: Evaluation of Service, Regulatory Understanding Factors, Sharia Financing Making Decisions